Juridical Review of Act No. 2 of 2014 concerning Notary Position Related to Confidentiality of Notary Duties - Yempi Yempi (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2020)
Protection of notaries related to confidentiality, especially in the law enforcement process, has not been able to be realized effectively, this is because there is no real protection system for notaries who disclose their secrets in the law enforcement process. This writing uses an empirical juridical method. As for the results of existing research, it can be found that the fact that the limitations of a notary in maintaining the confidentiality of a notary's duties based on the Notary's Position Law are that notaries must keep confidential what is related to their position. The notary is obliged to keep the contents of the deed secret, even the notary is obliged to keep all information from the preparation of the deed to the completion of the drafting of a deed and if he is made a witness in a case, can exercise his right to resign as a witness. However, it often happens that in a law enforcement process, a notary who is asked to assist in proof by disclosing the confidentiality of a deed that he has made can be sued and threatened by legal sanctions both in civil terms, namely acts against the law or on criminal grounds. So it is necessary to do more real legal protection for notaries who disclose the confidentiality of the deeds they have made for the sake of law enforcement. a notary who is asked to assist in the matter of proof by disclosing the confidentiality of the deed he has made can be sued and threatened with legal sanctions both in civil terms, namely acts against the law or on criminal grounds. So it is necessary to do more real legal protection for notaries who disclose the confidentiality of the deeds they have made for the sake of law enforcement. a notary who is asked to assist in the matter of proof by disclosing the confidentiality of the deed he has made can be sued and threatened with legal sanctions both in civil terms, namely acts against the law or on criminal grounds. So it is necessary to do more real legal protection for notaries who disclose the confidentiality of the deeds they have made for the sake of law enforcement.